Rāmāyaṇa and Mahābhārata in Stone: The Narrative Friezes of the Kṛṣṇa Temple at Pāṭan, Nepal - Berg, Jessica (Ergon-Verlag, 2022)
The book deals with the narrative friezes depicting the two great Indian epics, Rāmāyaṇa and Mahābhārata, on the 1637 built Kṛṣṇa temple, one of the most important monuments in the Kathmandu Valley. The friezes are outstanding in many ways: they are the only comprehensive Nepalese representations of this subject, and the Mahābhārata cycle is by far the most extensive in all of South Asia. The book includes illustrations of all 255 scenes, detailed descriptions, and comparisons with Indian precedents, focusing on local traditions. While some variations have a long history, others are less popular, and additionally, the representations include scenes that are not pictured elsewhere.